(untitled) - Joe Harris (New York, 1996)
This book introduces the algebraic geometry, it gives a sense of the basic objects considered, the questions asked about them, and the sort of answers one can expect to obtain. This book provides a basis for understanding the developments of the last haft century, which have put the subject on a radically new footing
Keywords: geometry, algebraic